Prevalence and Correlates of β– and γ–Human Papillomavirus Detection in Oral Samples From Mid-Adult Women. (31st October 2018) - Winer, Rachel L; Gheit, Tarik; Feng, Qinghua; Stern, Joshua E; Lin, John; Cherne, Stephen; Tommasino, Massimo
Abstract: Background: Little is known about the epidemiology of β and γ human papillomaviruses (HPVs) in oral cavities of healthy women. Methods: We performed multiplex polymerase chain reaction analysis for detection of 46 β-HPVs and 51 γ-HPVs in stored oral rinse samples from healthy mid-adult women (age, 30–50 years). A total of 407 women were tested for β-HPVs, and 310 were tested for γ-HPVs. We used log-binomial regression to identify determinants of β-HPV and γ-HPV in separate models. Using paired fingernail data from a subset of 184 women, we also evaluated whether fingernail β-HPV detection was associated with concurrent detection of the same type in the oral cavity. Results: Oral HPV prevalence was 20.6% for β-HPV and 10.7% for γ-HPV. In multivariate analysis, oral β-HPV detection was associated with increasing age (adjusted prevalence ratio [aPR] per 5-year difference, 1.37; 95% confidence interval [CI], 1.01–1.86) and a greater lifetime number of oral sex partners (aPR for reporting ≥6 vs 0–5 partners, 2.06; 95% CI, 1.01–4.20). In a separate model, concurrent detection of the same β-HPV type in fingernails was strongly associated with oral β-HPV detection (aPR, 31.44; 95% CI, 19.81–49.49). No significant determinants of γ-HPV detection were identified. Conclusions: Our results suggest a sexual transmission route for β-HPVs and support the hypothesis that fingers may serve as a source of transmission or autoinoculation of β-HPVs to the oral cavity. Abstract : β– and γ–human papillomaviruses (HPVs) were common in oral samples from healthy mid-adult women. Oral β-HPV detection was associated with increasing age, greater lifetime number of oral sex partners, and concurrent detection of the same β-HPV type in fingernails.